PENINGKATAN INDIVIDUAL PERFORMANCE MELALUI KNOWLEDGE SHARING DAN INNOVATION CAPABILITY - Syahriati Ramadhan (Jurnal Riset Bisnis Indonesia, 2015)
This study aims to examine and analyze the influence of variables Knowledge sharing, Innovation Capabilityand Individual Performance in the Regional Employment Board Muna, Southeast Sulawesi Province.Research was conducted on all employees of the Regional Employment Board Muna. The datacollection was done by distributing questionnaires to 54 respondents as sample. Sampling usingcensus method analysis model with Smart PLS (Partial Least Square) as a tool for analysis. Basedon the results of the analysis showed that the Knowledge sharing significant positive effect onInnovation Capability, Knowledge sharing, however no significant effect on Individual Performance.Then Innovation Capability significant effect on Individual Performance. Thus to improve theIndividual Performance can be done through Knowledge Sharing Innovation Capability by increasingemployee.Keywords: Knowledge sharing, Innovation Capability, dan Individual Performance.